2022
DOI: 10.1186/s12931-022-02015-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly improving acute respiratory distress syndrome in COVID-19: a multi-centre observational study

Abstract: Background Before the pandemic of coronavirus disease (COVID-19), rapidly improving acute respiratory distress syndrome (ARDS), mostly defined by early extubation, had been recognized as an increasingly prevalent subphenotype (making up 15–24% of all ARDS cases), associated with good prognosis (10% mortality in ARDSNet trials). We attempted to determine the prevalence and prognosis of rapidly improving ARDS and of persistent severe ARDS related to COVID-19. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…This finding is important because evidence both before and during the COVID-19 era showed that, among patients with ARDS, oxygenation on the third day after intubation may be more strongly associated with mortality than oxygenation on the day of intubation. 16,17 Also, the occurrence of bacteremia among survivors was 57.1% (8 of 14) in the full vaccination group vs 73.9% (65 of 88) in the control group, and, although statistically insignificant, this difference in occurrence might be associated with different mortality rates between groups. 18…”
Section: Jama Network Open | Critical Care Medicinementioning
confidence: 92%
“…This finding is important because evidence both before and during the COVID-19 era showed that, among patients with ARDS, oxygenation on the third day after intubation may be more strongly associated with mortality than oxygenation on the day of intubation. 16,17 Also, the occurrence of bacteremia among survivors was 57.1% (8 of 14) in the full vaccination group vs 73.9% (65 of 88) in the control group, and, although statistically insignificant, this difference in occurrence might be associated with different mortality rates between groups. 18…”
Section: Jama Network Open | Critical Care Medicinementioning
confidence: 92%
“…The second cohort of our study (“CARDS” cohort) consisted of patients with ARDS related to COVID-19 admitted between October 2020 and January 2022 (i.e., when the alpha and delta Sars-Cov-2 variants were prominent) in two academic intensive care units (ICU) at tertiary hospitals in Crete and Ioannina, Greece. Part of data from those patients have been included in previously published observational studies [ 14 , 15 ]. The Institutional Review Board at each participating study site (Ioannina: University Hospital of Ioannina, and Crete: University Hospital of Heraklion) approved of the data collection and waived the need for informed consent owing to the observational study design and the collection of de-identified data.…”
Section: Methodsmentioning
confidence: 99%
“…the patient had rapidly improving ARDS. This subphenotype of rapidly improving ARDS had been recognized before the pandemic as increasingly prevalent (15-24% of all ARDS cases) 7 , even though it appears less prevalent during the pandemic 8 . Also, prone ventilation led to lung recruitment allowing for a decrease of external PEEP by 3 cmH 2 O while maintaining positive transpulmonary pressure at end-expiration.…”
Section: Discussionmentioning
confidence: 98%